Using Guessing word in Learning Vocabulary At The English Club of SMPN 14 Kota Serang - Adi Manarul Fikri; Nurhaeda Gailea; Ahmad Maulana Jibriel; Fitra Aulia Rivani; Revi Oktaviani Mariska; Nur Alifah Maasah; Tasmi (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
This problem was caused in this research were based on condition of Students at the SMPN 14 Kota Serang in their vocabulary. Based on the class observation and questioners have been collected, there are some problem has been found. One of the cases are the students in English Club have considered low on vocabulary and lack of activity that can support their vocabulary learning. According to Grabe and Stoller’s (2019) stated that the vocabulary is an critical for the students to comprehension written expression in English. This also considered as the key of success in learning a foreign language. In this research, the researcher tries to implemented “Guessing Word” students in English Club activity every Wednesday after the school hours. This activity were need the student’s to make a list of some vocabulary such vocab around the school, house, park, and etc. Then the data is collected by sharing the questionnaire with Sixteen English Club students in 8th grade and interviews with some students to know their perception of difficulties in English vocabulary. The findings demonstrate that, the majority of respondents strongly agreed that vocabulary mastery had a big influence on their English proficiency. The implications of these findings for future of learning activity for student vocabulary.